Intraocular mutual burden syndrome in case of a gunshot penetrating injury of the eyeball in an experiment - A. A. Kol’bin; A. N. Kulikov; R. L. Troyanovsky (Российский офтальмологический журнал, 2025)
Purpose of the work is to analyze the features of a reproducible model of a penetrating gunshot wound of the eyeball without an intraocular foreign body (type B open eye injury). Material and methods. A comprehensive examination of 36 rabbits (71 eyes) was conducted with a previously developed reproducible model of a penetrating gunshot wound of the eye without an intraocular foreign body. To study the features of the experimental model and their dynamics, an examination was carried out at control periods, including biomicroscopy, reverse ophthalmoscopy and tonometry. Results. High reproducibility of the characteristic indicators (77.0–100 %) was shown, confirming the standardization of the developed model. The studied features of the model made it possible to register pathological changes in most structures of the eyeball, including proliferative changes. This justifies the need and legitimacy of using the term “intraocular mutual burden syndrome”. Conclusion. The described “syndrome of intraocular mutual burdening” is one of the reasons for low functional and anatomical outcomes of open gunshot eye trauma. The high frequency of occurrence of this pathology during combat operations and in peacetime justifies the need to continue its study. The developed standardized model of penetrating gunshot wound of the eye without an intraocular foreign body using modern ophthalmological and general clinical research methods can be used as a basis for the experiment.